Pervasive laboratory inventory for computer science (PLICS) - Baylosis, Patricia (2006)
Pervasive computing is all about making our lives easier by means of digital surroundings that are perceptive, adaptive and receptive to human needs. This technology will revolutionize the nature of computing by allowing objects that we come across in our daily lives to be responsive. It is a concept in the computing technology that aims to develop applications that require minimal human intervention and provide access to information anytime and anywhere. Its greatest distinction from the traditional computing is that pervasive computing requires perceptual information from its surrounding environment. This gathered information is what we call context information and pervasive systems must be able to use these contexts efficiently to interact with the user. Unfortunately, due to an ever-changing computing environment this becomes difficult to achieve. Thus, frameworks have been built to overcome this dilemma. Examples of these frameworks are One, World and Context Toolkit. These two are the platforms that we have chosen to use in our research. One world is centered on supporting context changes, allowing users to use applications written in this platform with any type of devices and share information easily. On the other hand, Context Toolkit aims to assist the developmemt and deployment of applications that are perceptive and adaptive to environmental information using context widgets. Context widgets are software components that separate the details of sensing context from actually using this context information. Both of these frameworks are written in Java and are open-source software thus they can easily be downloaded from the Internet for free. Several papers, source codes and other resources of One.world and Context Toolkit are also available in the Internet. Given these characteristics, we all have agreed to utilize the said frameworks. To demonstrate how pervasive computing can benefit us in many ways, we have built an automated inventory system specifically designed for monitoring items in a computer laboratory. We have used the One.World framework and the Context Toolkit framework to create two versions of the system and to see the capabilities, advantages and disadvantages in using these frameworks for pervasive applications development.